Conflict matrix as a mechanism of identifying the conflict in emotions of written text - Mohsin Manshad, Abbasi; Anees Qumar, Abbasi; Anatoly Petrovich, Beltiukov; Lal., Hussain (International Journal of Engineering and Technology, 2020)
Text is a major source of information and is considered as a mechanism of communicating emotions and ideas. The emotion and their analysis from written text gained popularity over recent decades. It has been credited to the growth of information technology and the rapid increase in availability of internet around the globe. In this work, the main idea is to identify the conflict in emotions that exist in the written text. The use of conflict analysis is to identify the contradictory views of people about an object or a topic of discussion. Its existence in text however complicates the process of analysis of emotions from text. This paper describes a mechanism in which the emotions in each pair of sentence are considered as conflicting to each other. The emotional orientation of each pair of sentence is observed to identify the truth-value of the proposed conflict hypothesis. The result of the analysis is summarized using the Conflict matrix. Conflict matrix is a major product of this research that is used to identify the conflicting emotions in text and to measure their characteristics. The results of the experiment were analyzed using the supervised learning techniques along with the Confusion matrix. In methodology and conclusion sections of the paper, the results are discussed in detail.Â Â